Graphene composite conductive material and preparation method thereof

By combining the MnO2/graphene composite material with graphite powder, polyimide and filler, graphene composite conductive materials with high conductivity and mechanical properties were prepared, which solved the shortcomings of existing materials in conductivity and mechanical properties and achieved the wide application potential of materials.

CN119673528AInactive Publication Date: 2025-03-21李恒飞
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411951283.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing graphene composite conductive materials have shortcomings in terms of conductivity, mechanical properties, processability, etc., which are difficult to meet the needs of high conductivity and mechanical properties. The preparation process is complex and the cost is high, which limits its wide application.

Method used

The combined design of MnO2/graphene composite material, graphite powder, polyimide and filler is used for a combined design. Graphene composite conductive materials are prepared through ultrasonic dispersion, hydrothermal reaction, glue impregnation method and thermal molding, forming a three-dimensional conductive network and enhanced phase to improve conductivity and mechanical properties.

Benefits of technology

The prepared graphene composite conductive materials have good conductivity, mechanical properties and stability, adapt to a variety of complex environments, are low-cost and easy to handle and recycle, and are suitable for energy storage, catalysis, sensors and electromagnetic shielding and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673528A_ABST
    Figure CN119673528A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive materials, and particularly relates to a graphene composite conductive material and a preparation method thereof.The graphene composite conductive material is prepared from, by weight, 12-25 parts of MnO2 / graphene composite material, 15-25 parts of graphite powder, 35-50 parts of macromolecule resin and 1-8 parts of filler, according to the MnO2 / graphene composite material, the electron migration efficiency is improved by utilizing the huge specific surface area of graphene, MnO2 particles uniformly grow on a graphene sheet layer, agglomeration and accumulation of the graphene sheet layer in the compounding process can be prevented by uniform loading of MnO2, an effective conductive path is formed by graphite powder and the graphene layer, and the conductivity of the composite material is improved. Functional groups on the surfaces of the graphene and MnO2 are chemically bonded with a macromolecular resin molecular chain, so that the interface interaction is enhanced, and the used filler has relatively high strength and modulus and is used as a reinforcing phase to improve the mechanical property of the graphene composite conductive material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of conductive materials, and in particular relates to a graphene composite conductive material and a preparation method thereof. Background Art

[0002] As a two-dimensional carbon material, graphene is considered to be an ideal conductive filler due to its unique two-dimensional structure and excellent physical and chemical properties, such as extremely high electrical conductivity, large specific surface area, good mechanical strength and chemical stability. The carbon six-ring structure of defect-free single-layer graphene is almost perfect, and it is difficult to change its structure easily under the connection of each carbon. It exhibits extremely high tensile strength and compressive strength on a macro scale. Graphene also has excellent electrical conductivity. Each carbon atom in the single-layer graphene structure provides an unbonded electron, which can move freely in the crystal, showing good electrical conductivity on a macro scale. Graphene also has excellent thermal conductivity properties. Since graphene has no crystal defects and has a very stable two-dimensional crystal structure, these properties contribute to its good thermal conductivity.

[0003] However, pure graphene materials have problems such as poor dispersibility and difficulty in processing in practical applications. Therefore, in order to overcome the limitations of a single material, researchers began to explore the combination of graphene with other materials to prepare composite conductive materials with excellent comprehensive performance. These composite materials can combine the high conductivity of graphene with the mechanical properties and thermal stability of other materials, but the existing graphene composite conductive materials still have the following deficiencies in conductivity, mechanical properties, and processability: limited improvement in conductivity, which makes it difficult to meet the needs of high conductivity applications, insufficient mechanical properties, especially in the field of flexible conductive materials, complex preparation processes, and difficulty in large-scale production. The high material cost limits its wide application in certain fields. Therefore, it is urgent to develop a graphene composite conductive material with good conductivity and high mechanical properties. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a graphene composite conductive material and a preparation method thereof. The present invention adopts MnO2 / graphene composite material, graphite powder, polyimide and filler for combination design, and uses MnO2 / graphene composite material and other materials to prepare graphene composite conductive material together. Graphite powder, as part of the conductive network, forms an effective conductive path with the graphene layer of the MnO2 / graphene composite material. MnO2 can interact with defective parts on graphene to improve the electrochemical properties of the overall material. Polyimide, as a matrix material, provides mechanical strength and thermal stability, and fixes graphene and MnO2 particles at the same time to enhance the stability of the graphene composite conductive material. The filler has high strength and modulus, and as a reinforcing phase, it improves the mechanical properties of the graphene composite conductive material. The conductive properties of the filler form a three-dimensional conductive network with graphene and graphite powder to further improve the overall conductivity. The graphene composite conductive material prepared by the present invention has good environmental stability, can maintain performance under different environmental conditions, and is easy to handle and recycle.

[0005] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows: The present invention provides a graphene composite conductive material, which is prepared from the following raw materials in parts by weight: 12-25 parts of MnO2 / graphene composite material, 15-25 parts of graphite powder, 35-50 parts of polymer resin, 1-8 parts of filler, and 1-3 parts of coupling agent; Preferably, the fineness of the graphite powder is 500-2000 mesh.

[0006] Preferably, the polymer resin is at least one of polyimide and LCP (liquid crystal polymer).

[0007] Preferably, the filler is at least one of carbon fiber mesh, copper mesh and nickel mesh.

[0008] Preferably, the coupling agent is at least one of KH-550 (γ-aminopropyltriethoxysilane), A151 (γ-chloropropylmethyldiethoxysilane) and KH-570 (vinyltriethoxysilane).

[0009] Furthermore, the raw materials for preparing the MnO2 / graphene composite material are: graphene and MnO2.

[0010] The preparation method of the MnO2 / graphene composite material specifically comprises the following steps: (1) Ultrasonic dispersion of graphene in anhydrous ethanol for 1-2 h, with the ratio of graphene to anhydrous ethanol being 1 g:35 mL, to form a dispersion, and MnO2 is added to the dispersion, and magnetic stirring is performed to form a uniform reaction mixture. (2) The reaction mixture obtained in step (1) is transferred into a Teflon-lined stainless steel autoclave for hydrothermal reaction at 200 °C for 24 h. After cooling to room temperature, the mixture is washed, centrifuged, and dried in an oven to obtain a MnO2 / graphene composite material.

[0011] Furthermore, the mass ratio of MnO2 to the dispersion is 2-5:19.

[0012] The present invention also provides a method for preparing a graphene composite conductive material, which specifically comprises the following steps: S1, weighing graphite powder by weight and ultrasonically dispersing it in deionized water for 1 h, with the mass ratio of graphite powder to deionized water being 1:20, to form a suspension, adding polymer resin and coupling agent by weight to the suspension, and then rapidly stirring at a speed of 1000 rpm for 30 min to obtain a mixture A; S2, weighing MnO2 / graphene composite material by weight and adding it to DMF (NN dimethylformamide), ultrasonically dispersing for 30-60 min to form mixture B, adding mixture A obtained in step S1 to mixture B, and stirring at a constant temperature to obtain mixture C; S3, weighing the filler by weight, and impregnating the mixture C obtained in step S2 on the filler by a dipping method, controlling the time to be 10-20 min, the pressure to be 0.1-0.5 MPa, and the temperature to be 50°C, drying at room temperature after impregnation to form a reaction precursor, loading the reaction precursor into a molding mold, and performing hot compression molding on a high-temperature mechanical pressure vulcanizer to obtain a graphene composite conductive material.

[0013] Furthermore, the usage ratio of the MnO2 / graphene composite material to DMF is 1 g:20-30 mL.

[0014] Furthermore, the hot compression molding method heats the mold from room temperature to 200°C at a heating rate of 10°C / min, keeps the temperature at 20 MPa for 10 min, releases the pressure and exhausts the air multiple times during the process, then heats up to 300°C and keeps the temperature for 40 min, cools to room temperature and demolds the sample after the heat and pressure are completed, and then places the sample in an oven and heats up to 200°C and keeps the temperature for 60 min, then heats up to 220°C and keeps the temperature for 120 min, cools to room temperature and takes out.

[0015] Furthermore, the high-temperature mechanical pressure vulcanizing machine is of model OLLHY-50T.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The graphene composite conductive material prepared by the present invention is designed by combining materials such as MnO2 / graphene composite material, graphite powder, polymer resin and filler. The graphene composite conductive material is prepared by using the MnO2 / graphene composite material and other materials together. The prepared graphene composite conductive material has good electrochemical performance and good mechanical performance. The graphite powder, as a part of the conductive network, forms an effective conductive path with the graphene layer of the MnO2 / graphene composite material. MnO2 can interact with defective parts on the graphene to improve the electrochemical performance of the overall material. The functional groups on the surfaces of graphene and MnO2 can chemically bond with the polymer resin molecular chains to enhance the interface interaction. The polymer resin, as a part of the conductive network, forms an effective conductive path with the graphene layer of the MnO2 / graphene composite material. The matrix material provides mechanical strength and thermal stability, while fixing graphene and MnO2 particles to enhance the stability of graphene composite conductive materials. The filler has high strength and modulus, and as a reinforcing phase, it improves the mechanical properties of graphene composite conductive materials. The conductive properties of the filler form a three-dimensional conductive network with graphene and graphite powder, further improving the overall conductivity. The MnO2 / graphene composite material can well maintain the characteristics of MnO2 and graphene sheets, and use the huge specific surface area of ​​graphene to improve the efficiency of electron migration. Not only does it make the MnO2 particles grow evenly on the graphene sheets, but the uniform loading of MnO2 can prevent the agglomeration and accumulation of graphene sheets during the composite process, indirectly increasing the loading of Mn on the graphene sheets. 2+Active sites, at the same time, graphene sheets are interconnected to form a conductive network, so that the composite material has good conductivity. The large specific surface area of ​​graphene flake structure as the skeleton of MnO2 / graphene composite material can support MnO2, can quickly transfer photogenerated electrons, reduce the recombination efficiency of electron holes, and thus improve the dispersion and conductivity of MnO2. The two-dimensional layered structure of graphene can provide support for MnO2 to prevent its volume expansion and structural collapse during the electrochemical reaction, thereby improving the cycle stability and service life of the material. Graphene has an extremely high specific surface area and can load more MnO2, providing more active sites, thereby improving the overall performance of the composite conductive material. The conductivity of graphene The electrical network helps electrons to be quickly transmitted between MnO2 particles, reduces the charge transmission resistance, and improves the reaction efficiency of the electrode material. Graphene can be used as a carrier to help MnO2 particles disperse evenly and prevent agglomeration, thereby improving the utilization rate and performance of the composite conductive material; the combination of graphene and MnO2 improves the performance of the material at high temperatures, and the added polymer resin itself has excellent thermal stability, which further improves the stability of the composite conductive material. Through the interaction between materials, the interface performance is optimized, the internal stress is reduced, and the conductive filler is prevented from falling off and agglomerating. The graphene composite conductive material has good environmental stability, can maintain performance under different environmental conditions, and is easy to handle and recycle. The present invention provides a graphene composite conductive material with excellent electrochemical performance and simple synthesis process, the preparation method is simple, the cost is low and it is environmentally friendly, the prepared graphene composite conductive material has strong conductivity, high mechanical strength and good stability, and this graphene composite conductive material can be used not only for energy storage, but also for catalysis, sensors, electromagnetic shielding and other fields, and has a wide range of application potentials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the conductivity of the graphene composite conductive materials prepared in Example 1 and Comparative Examples 1-3 of the present invention; Figure 2 A schematic diagram of the stability of the graphene composite conductive materials prepared in Example 1 and Comparative Examples 1-3 of the present invention; Figure 3 Schematic diagram of thermal conductivity of graphene composite conductive materials prepared in Example 1 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0018] In order to make the technical solution of the present invention better understood by the technical personnel in the field, and to make the above-mentioned features, purposes and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the embodiments. The embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0019] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0020] Example 1: This example provides a graphene composite conductive material, which is prepared from the following raw materials in parts by weight: 12 parts of MnO2 / graphene composite material, 15 parts of graphite powder, 35 parts of polyimide, 1 part of carbon fiber mesh, and 1 part of KH-550; The fineness of the graphite powder is 2000 mesh; The raw materials for preparing the MnO2 / graphene composite material are: graphene and MnO2; The preparation method of the MnO2 / graphene composite material specifically comprises the following steps: (1) Ultrasonic dispersion of graphene in anhydrous ethanol was performed in an ultrasonic cleaning machine for 1 h. The power was set to 240 W. The ratio of graphene to anhydrous ethanol was 1 g:35 mL to form a dispersion. MnO2 was added to the dispersion at a mass ratio of MnO2 to the dispersion of 2:19. The mixture was stirred with a magnetic stirrer at 60 °C and 800 rpm to form a uniform reaction mixture. (2) The reaction mixture obtained in step (1) was transferred into a Teflon-lined stainless steel autoclave for hydrothermal reaction and maintained at 200°C for 24 h. After cooling to room temperature, the mixture was washed alternately by centrifugation with deionized water and anhydrous ethanol, and dried in a 70°C oven for 24 h to obtain a MnO2 / graphene composite material.

[0021] This embodiment also provides a method for preparing a graphene composite conductive material, which specifically comprises the following steps: S1, weigh 15 parts of graphite powder and ultrasonically disperse them in deionized water for 1 h, the mass ratio of graphite powder to deionized water is 1:20, to form a suspension, add 35 parts of polyethylamine and 1 part of KH-550 to the suspension, and then rapidly stir at a speed of 1000 rpm for 30 min to obtain a mixture A; S2, weighing 12 parts of MnO2 / graphene composite material and adding them to DMF, the amount ratio of MnO2 / graphene composite material to DMF is 1 g:20 mL, in an ultrasonic cleaning machine, ultrasonically disperse for 30 min, the power is set to 240 W, to form a mixture B, adding the mixture A obtained in step S1 to the mixture B, stirring at 800 rpm at 60 ° C, to obtain a mixture C; S3, take 1 portion of carbon fiber mesh, and soak the mixture C obtained in step S2 on the carbon fiber mesh. The carbon fiber mesh is pre-soaked and cleaned with acetone, dried and used, and soaked by a dipping method, with a control time of 10 min, a pressure of 0.1 MPa, and a temperature of 50 ° C. After soaking, it is dried at room temperature to form a reaction precursor, and the reaction precursor is loaded into a molding mold, and hot molding is performed on a high-temperature mechanical press vulcanizer. The hot molding is performed by heating the mold from room temperature to 200 ° C at a heating rate of 10 ° C / min, and keeping the temperature and pressure at 20 MPa for 10 min, during which the pressure is released and exhausted for multiple times, and then the temperature is raised to 300 ° C and kept at a temperature and pressure for 40 min. After the heat preservation and pressure retention is completed, it is cooled to room temperature for demolding, and then the sample is placed in an oven and freely heated to 200 ° C and kept for 60 min, and then heated to 220 ° C and kept for 120 min. After the oven is cooled to room temperature, it is taken out to obtain a graphene composite conductive material.

[0022] Example 2: This example provides a graphene composite conductive material, which is prepared from the following raw materials in parts by weight: 18 parts of MnO2 / graphene composite material, 20 parts of graphite powder, 42 parts of polyimide, 5 parts of copper wire mesh, and 2 parts of A151; The fineness of the graphite powder is 1000 mesh; The raw materials for preparing the MnO2 / graphene composite material are: graphene and MnO2; The preparation method of the MnO2 / graphene composite material specifically comprises the following steps: (1) Graphene was ultrasonically dispersed in anhydrous ethanol in an ultrasonic cleaning machine for 1 h, the power was set to 240 W, the amount ratio of graphene to anhydrous ethanol was 1 g:35 mL, and a dispersion was formed. MnO2 was added to the dispersion, and the mass ratio of MnO2 to the dispersion was 3:19. The mixture was stirred with a magnetic stirrer at 60 °C and 800 rpm to form a uniform reaction mixture. (2) The reaction mixture obtained in step (1) was transferred into a Teflon-lined stainless steel autoclave for hydrothermal reaction and maintained at 200°C for 24 h. After cooling to room temperature, the mixture was washed alternately by centrifugation with deionized water and anhydrous ethanol, and dried in a 70°C oven for 24 h to obtain a MnO2 / graphene composite material.

[0023] This embodiment also provides a method for preparing a graphene composite conductive material, which specifically comprises the following steps: S1, weigh 20 parts of graphite powder and ultrasonically disperse them in deionized water for 1 h, the mass ratio of graphite powder to deionized water is 1:20, to form a suspension, add 42 parts of polyimide and 2 parts of A151 to the suspension, and then rapidly stir at a speed of 1000 rpm for 30 min to obtain a mixture A; S2, weighing 18 parts of MnO2 / graphene composite material and adding them to DMF, the amount ratio of MnO2 / graphene composite material to DMF is 1 g:25 mL, in an ultrasonic cleaning machine, ultrasonically disperse for 45 min, the power is set to 240 W, to form a mixture B, adding the mixture A obtained in step S1 to the mixture B, stirring at 800 rpm at 60 ° C, to obtain a mixture C; S3, take 5 portions of copper wire mesh, and infiltrate the mixture C obtained in step S2 on the copper wire mesh, the copper wire mesh is pre-soaked and cleaned with acetone, and used after drying, and infiltrated by a dip method, the control time is 15 min, the pressure is 0.2 MPa, and the temperature is 50°C. After infiltration, it is dried at room temperature to form a reaction precursor, and the reaction precursor is loaded into a molding mold, and hot molding is performed on a high-temperature mechanical press vulcanizer. The hot molding is performed by heating the mold from room temperature to 200°C at a heating rate of 10°C / min, and keeping the temperature and pressure at 20 MPa for 10 min, during which the pressure is released and exhausted for multiple times, and then the temperature is increased to 300°C and kept at a temperature and pressure for 40 min. After the heat preservation and pressure retention is completed, it is cooled to room temperature for demoulding, and then the sample is placed in an oven and freely heated to 200°C and kept for 60 min, and then heated to 220°C and kept for 120 min. After the oven is cooled to room temperature, it is taken out to obtain a graphene composite conductive material.

[0024] Example 3: This example provides a graphene composite conductive material, which is prepared from the following raw materials in parts by weight: 25 parts of MnO2 / graphene composite material, 25 parts of graphite powder, 50 parts of LCP, 8 parts of nickel wire mesh, and 3 parts of KH-570; The fineness of the graphite powder is 500 mesh; The raw materials for preparing the MnO2 / graphene composite material are: graphene and MnO2; The preparation method of the MnO2 / graphene composite material specifically comprises the following steps: (1) Ultrasonic dispersion of graphene in anhydrous ethanol was performed in an ultrasonic cleaning machine for 1 h. The power was set to 240 W. The ratio of graphene to anhydrous ethanol was 1 g:35 mL to form a dispersion. MnO2 was added to the dispersion. The mass ratio of MnO2 to the dispersion was 5:19. The mixture was stirred with a magnetic stirrer at 60 °C and 800 rpm to form a uniform reaction mixture. (2) The reaction mixture obtained in step (1) was transferred into a Teflon-lined stainless steel autoclave for hydrothermal reaction and maintained at 200°C for 24 h. After cooling to room temperature, the mixture was washed alternately by centrifugation with deionized water and anhydrous ethanol, and dried in a 70°C oven for 24 h to obtain a MnO2 / graphene composite material.

[0025] This embodiment also provides a method for preparing a graphene composite conductive material, which specifically comprises the following steps: S1, weigh 15 parts of graphite powder and ultrasonically disperse them in deionized water for 1 h, the mass ratio of graphite powder to deionized water is 1:20, to form a suspension, add 50 parts of LCP and 3 parts of KH-570 to the suspension, and then rapidly stir at a speed of 1000 rpm for 30 minutes to obtain a mixture A; S2, weighing 25 parts of MnO2 / graphene composite material and adding them to DMF, the amount ratio of MnO2 / graphene composite material to DMF is 1 g:30 mL, in an ultrasonic cleaning machine, ultrasonically disperse for 60 min, the power is set to 240 W, to form a mixture B, adding the mixture A obtained in step S1 to the mixture B, stirring at 800 rpm at 60 ° C, to obtain a mixture C; S3, take 8 parts of nickel wire mesh, and soak the mixture C obtained in step S2 on the nickel wire mesh. The nickel wire mesh is pre-soaked and cleaned with acetone, dried and used, and soaked by a dip method, with a control time of 20 min, a pressure of 0.5 MPa, and a temperature of 50°C. After soaking, it is dried at room temperature to form a reaction precursor, and the reaction precursor is loaded into a molding mold, and hot molding is performed on a high-temperature mechanical press vulcanizer. The hot molding is performed by heating the mold from room temperature to 200°C at a heating rate of 10°C / min, and keeping the temperature and pressure at 20 MPa for 10 min, during which the pressure is released and exhausted for multiple times, and then the temperature is raised to 300°C and kept at a temperature and pressure for 40 min. After the heat preservation and pressure retention is completed, it is cooled to room temperature for demolding, and then the sample is placed in an oven and freely heated to 200°C and kept for 60 min, and then heated to 220°C and kept for 120 min. After the oven is cooled to room temperature, it is taken out to obtain a graphene composite conductive material.

[0026] The difference between Comparative Example 1 and Example 1 is that the addition of MnO2 is eliminated, and the rest is the same as Example 1.

[0027] The difference between Comparative Example 2 and Example 1 is that the addition of polymer resin is eliminated, and the rest is the same as Example 1.

[0028] The difference between Comparative Example 3 and Example 1 is that the addition of filler is eliminated, and the rest is the same as Example 1.

[0029] Experimental Example 1: The conductivity of the samples of Examples 1-3 and Comparative Examples 1-3 was tested using a TechRST-8 four-probe resistivity tester, and the thermal conductivity of the samples of Examples 1-3 and Comparative Examples 1-3 was tested using a PPMS-9T physical property testing system produced by QUANTUMDESIGN, USA; Testing principle: A heat pulse is applied to the surface of one side of the product, and the heat is transferred to the surface of the other side. The system collects the temperature difference in the sample and calculates the thermal conductivity of the material according to the geometric shape of the sample. The conductivity results are as follows: Figure 1 The thermal conductivity results are shown in Figure 3 shown.

[0030] Experimental Example 2: According to the national standard GB\T 453-2002 "Determination of tensile strength of paper and paper", the tensile strength of the graphene composite conductive material prepared by the present invention is tested. The graphene composite conductive materials prepared by Examples 1-3 and Comparative Examples 1-3 are used as test samples. The tensile strength of the samples is tested under constant speed conditions using a tensile strength tester. The load of the clamp is adjusted. During the test, the sample is ensured to be neither slipped nor damaged. An appropriate weight is clamped on the clamp. The weight drives the loading indicator to record its reading. The test is carried out under standard atmospheric conditions for temperature and humidity treatment of the sample. The zero position and front and rear levels of the measuring mechanism and the recording device are checked. The distance between the upper and lower clamps is adjusted, and the sample is clamped in the clamp to prevent the test area between the clamps from being touched by hand. A pretension of 98 mN is applied to the sample, and the sample is clamped vertically between the two clamps. A prediction test is first performed to find the loading speed at which the sample breaks within 20 s. From the start of the measurement to the time when the sample breaks, the maximum applied force is recorded. Calculate and express the results of paper and paperboard in the longitudinal and transverse directions respectively. The tensile strength is expressed by the formula S=F / L W Calculate, where S is the tensile strength in kN / m, F is the average tensile force in N, L W is the width of the sample in mm. The results are recorded in Table 1.

[0031] Experimental Example 3: Referring to GB / T 1040-92 standard, the graphene composite conductive materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 were used to make 1 mm specimens, and the specimens were made into dumbbell-shaped standard specimens using a CP-25 punching machine. Then, a tensile test was carried out on a microcomputer-controlled electronic universal testing machine (WDW-20); the maximum tensile force was 500 N, the tensile speed was 200 mm / min, and the basic size of the specimen was 100×6×1 mm. The elongation at break and the elastic modulus were measured, and the results are recorded in Table 1.

[0032] Experimental Example 4: The graphene composite conductive materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-3 were used as samples to test the maximum roughness of their bonding surfaces. Each sample was prepared into a material bonding surface and tested using a stylus-type surface roughness meter to ensure that the test samples were clean, dry, and free of any contaminants. The maximum roughness of the bonding surface was tested according to the instrument operating specifications, and the results were recorded in Table 1.

[0033] Table 1

[0034] The results in Table 1 show that the graphene composite conductive materials prepared by Examples 1-3 all exhibited excellent performances superior to those of the comparative examples in terms of three mechanical performance indicators: tensile strength, elongation at break and elastic modulus. This indicates that the material combination and preparation method adopted by the present invention can effectively improve the overall mechanical properties of the composite conductive materials. Specifically, the graphene composite conductive material prepared by Example 1 not only has a tensile strength significantly higher than that of the comparative example, which means that the material can withstand greater external forces without breaking easily, but also the improvement in elongation at break also indicates that the material has better flexibility and deformation ability. The increase in elastic modulus reflects the enhanced ability of the material to resist deformation when subjected to force, which helps to improve the stability and durability of the material. For the maximum value of the bonding surface roughness, the embodiments are all lower than the comparative example, indicating that the moderate maximum value of the bonding surface roughness of the embodiments balances the bonding and wettability and has good stability.

[0035] Figure 1 The conductivity diagram of Example 1 of the present invention and Comparative Examples 1-3 is shown. The conductivity of Example 1 is significantly higher than that of Comparative Examples 1-3, reaching 0.09 S / m, indicating that the interaction between the materials enhances the conductive path and increases the conductivity. The synergistic effect between the materials increases the conductivity of the graphene composite conductive material. Figure 2 The graph shows the change of volume resistivity with storage time. It can be seen that when the storage time of the graphene composite conductive material prepared in Example 1 of the present invention is less than 10 days, the resistivity of the composite conductive material gradually increases. When the storage time exceeds 10 days, the volume resistivity of the composite conductive material tends to be stable and basically maintains at 10 Ω·cm. The conductive stability of the composite conductive material is good. Figure 3 A schematic diagram of thermal conductivity is shown, and it can be seen that the thermal conductivity of Example 1 is significantly higher than that of the comparative example, indicating that the graphene composite material of Example 1 performs best in thermal conductivity and has a good ability to conduct heat.

[0036] In summary, the graphene composite conductive material prepared by the present invention not only has good conductivity, but also has excellent mechanical properties. Graphite powder and graphene are both good conductive materials, and the added MnO2 and graphene further improve the cyclic stability of the composite conductive material. Their addition significantly improves the conductivity of the composite material. The three-dimensional network structure of the filler is conducive to the transmission of electrons, thereby further improving the conductivity. The addition of the filler significantly improves the tensile strength, elastic modulus and impact resistance of the composite material. The polymer resin itself has excellent thermal stability. Through the interaction between materials, the interface performance can be optimized, the internal stress can be reduced, and the shedding and agglomeration of the conductive filler can be prevented. In addition, in practical applications, it can adapt to a variety of complex working environments and meet the strict requirements of different fields for the mechanical properties of materials. Whether it is used in electronic devices, aerospace, transportation or building materials, the conductive composite material has the potential to provide better performance solutions, thereby promoting technological progress and product innovation in related industries.

[0037] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A graphene composite conductive material, characterized in that: The graphene composite conductive material is prepared from the following raw materials in parts by weight: 12-25 parts of MnO2 / graphene composite material, 15-25 parts of graphite powder, 35-50 parts of polymer resin, 1-8 parts of filler, and 1-3 parts of coupling agent; The raw materials for preparing the MnO2 / graphene composite material are: graphene and MnO2; The preparation method of the MnO2 / graphene composite material specifically comprises the following steps: (1) Weighing graphene and ultrasonically dispersing it in anhydrous ethanol to form a dispersion, adding MnO2 to the dispersion, and magnetically stirring to form a uniform reaction mixture; (2) The reaction mixture obtained in step (1) is subjected to a hydrothermal reaction, and after being cooled to room temperature, it is washed, centrifuged, and dried to obtain a MnO2 / graphene composite material.

2. A graphene composite conductive material according to claim 1, characterized in that: In step (1), the usage ratio of graphene to anhydrous ethanol is 1 g:35 mL, and the mass ratio of MnO2 to dispersion is 2-5:

19.

3. The method for preparing the graphene composite conductive material according to claim 1, characterized in that: In step (2), the hydrothermal reaction is carried out in a Teflon-lined stainless steel autoclave, the temperature is set to 200°C, and the time is set to 24 h.

4. The graphene composite conductive material according to claim 1, characterized in that: The fineness of the graphite powder is 500-2000 meshes.

5. The graphene composite conductive material according to claim 1, characterized in that: The polymer resin is at least one of polyimide and LCP.

6. The graphene composite conductive material according to claim 1, characterized in that: The filler is at least one of a carbon fiber mesh, a copper mesh and a nickel mesh.

7. The graphene composite conductive material according to claim 1, characterized in that: The coupling agent is at least one of KH-550, A151 and KH-570.

8. A method for preparing the graphene composite conductive material according to any one of claims 1 to 7, characterized in that: The specific steps include: S1, weighing graphite powder by weight and dispersing it in deionized water by ultrasonic to form a suspension, adding a polymer resin and a coupling agent by weight to the suspension, and then rapidly stirring to obtain a mixture A; S2, weighing the MnO2 / graphene composite material by weight and adding it to DMF, ultrasonically dispersing it to form a mixture B, adding the mixture A obtained in step S1 to the mixture B, and stirring at a constant temperature to obtain a mixture C; S3, taking fillers by weight, impregnating the mixture C obtained in step S2 on the fillers by a dipping method, drying to form a reaction precursor, and hot-molding the reaction precursor to obtain a graphene composite conductive material.

9. The method for preparing the graphene composite conductive material according to claim 8, characterized in that: In step S2, the usage ratio of the MnO2 / graphene composite material to DMF is 1 g:20-30 mL.

10. The method for preparing the graphene composite conductive material according to claim 8, characterized in that: In step S3, the hot compression molding is performed by heating the mold from room temperature to 200°C at a heating rate of 10°C / min, keeping the temperature at 20 MPa for 10 minutes, venting the pressure and exhausting the air multiple times during the process, and then heating the mold to 300°C and keeping the temperature for 40 minutes. After the temperature and pressure are maintained, the mold is cooled to room temperature and demolded. The sample is then placed in an oven and freely heated to 200°C and kept for 60 minutes, then heated to 220°C and kept for 120 minutes, and then cooled to room temperature and taken out.

Citation Information

Patent Citations

  • Method for preparing manganese dioxide / graphene / porous carbon (MnO2 / rGO / C) composite material and application of MnO2 / rGO / C composite material to supercapacitor as electrode material

    CN104362001A

  • Supercapacitor

    CN106252096A

  • Hydrothermal synthesis method of alpha-MnO2-graphene nanosheet

    CN107275623A

  • Preparation method and application of electromagnetic shielding composite material with full-through characteristic

    CN115093678A

  • Metal-based polyvinylidene fluoride / conductive carbon powder / carbonized polyimide composite material as well as preparation method and application thereof

    CN118544674A